2017
DOI: 10.3389/fpls.2017.02056
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Sensitive Amplification Polymorphism Sequencing (MSAP-Seq)—A Method for High-Throughput Analysis of Differentially Methylated CCGG Sites in Plants with Large Genomes

Abstract: Epigenetic mechanisms, including histone modifications and DNA methylation, mutually regulate chromatin structure, maintain genome integrity, and affect gene expression and transposon mobility. Variations in DNA methylation within plant populations, as well as methylation in response to internal and external factors, are of increasing interest, especially in the crop research field. Methylation Sensitive Amplification Polymorphism (MSAP) is one of the most commonly used methods for assessing DNA methylation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 48 publications
0
32
0
1
Order By: Relevance
“…Finally, there are several variations of methylation‐sensitive amplified polymorphism (MSAP) that allow the parallel and direct analysis of DNAm for a high number of sites across the genome (Yaish, Peng & Rothstein, ). A variation of the MSAP approach that involves next generation sequencing and automated data analysis is a suitable option for plant species (Chwialkowska et al ., ). Methylation ‐sensitive amplified fragment length polymorphism (MS‐ AFLP) is a modification of amplification fragment length polymorphism (AFLP) that is based on DNA restrictive digestion with enzymes; this technique is also used to profile methylation patterns without requiring detailed knowledge of the genome sequence (Fulneček & Kovařík, ; Kurdyukov & Bullock, ).…”
Section: Sequencing Techniques Supporting the Development Of Dnam Biomentioning
confidence: 97%
“…Finally, there are several variations of methylation‐sensitive amplified polymorphism (MSAP) that allow the parallel and direct analysis of DNAm for a high number of sites across the genome (Yaish, Peng & Rothstein, ). A variation of the MSAP approach that involves next generation sequencing and automated data analysis is a suitable option for plant species (Chwialkowska et al ., ). Methylation ‐sensitive amplified fragment length polymorphism (MS‐ AFLP) is a modification of amplification fragment length polymorphism (AFLP) that is based on DNA restrictive digestion with enzymes; this technique is also used to profile methylation patterns without requiring detailed knowledge of the genome sequence (Fulneček & Kovařík, ; Kurdyukov & Bullock, ).…”
Section: Sequencing Techniques Supporting the Development Of Dnam Biomentioning
confidence: 97%
“…Many techniques have been developed to analyze global DNA methylation and its alterations [12]. The method of methylation-sensitive amplified polymorphism (MSAP) is one of the most efficient, economical, and widely one used for the detection of DNA methylation events [13][14]. This approach is a modified version of the amplified fragment length polymorphism (AFLP) method based on the differential sensitivity of isoschizomeric restriction endonucleases to site-specific cytosine methylation [15].…”
Section: Introductionmentioning
confidence: 99%
“…So, on the basis of variant band patterns resulting from differential digestion of the genome by HpaII/MspI isozymes, variation in the DNA methylation level and pattern in the whole genome is detected [15,17]. MSAP has been successfully applied for the analysis of the variation in methylation levels and patterns in a variety of plant species [13].…”
Section: Introductionmentioning
confidence: 99%
“…Analysing two wheat genotypes in combination with their somaclones, characterized by a changed heritable phenotype, the authors were able to study epigenetically induced changes and, at the same time, identify over 100 amplicons that were differentially methylated among the samples. Another MSAP-based approach combined with NGS is MSAP-Seq [ 14 ], which is also integrated with an automatic pipeline MSEQER. This method used conventional MSAP analysis (digestion of DNA with Eco RI and Hpa II enzymes) and replaced the gel separation of amplicons (from selective PCR) with NGS.…”
Section: Discussionmentioning
confidence: 99%
“…At the present, only two studies have reported the combined use of MSAP analysis and NGS in plants, but their results were limited to the identification of polymorphic amplicons, without the determination of the DNA methylation status of the sequenced fragments or the identification of the pathways that were enriched for differentially methylated sequences. In other studies, some authors applied bisulphite NGS sequencing after MSAP [ 13 ], particularly when the genome sequence was known, as in the case of rice as an alternative, they proceeded with amplicon electrophoresis on polyacrylamide gels and the isolation of polymorphic bands, then sequenced through Sanger technology [ 14 ]. Our study promises to make a step forward in this kind of molecular analysis, providing a new protocol of coupled MSAP-NGS and a new flowchart for data mining, useful for obtaining information about the methylation status of the sequenced fragments and their involvement in specific genetic pathways and biological processes.…”
Section: Introductionmentioning
confidence: 99%